2022
DOI: 10.21037/cdt-21-505
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coronary plaque morphology on the precision of computational fractional flow reserve derived from optical coherence tomography imaging

Abstract: Background: Computational fractional flow reserve (FFR) was recently developed to expand the use of physiology-guided percutaneous coronary intervention (PCI). Nevertheless, current methods do not account for plaque composition. It remains unknown whether the numerical precision of computational FFR is impacted by the plaque composition in the interrogated vessels.Methods: This study is an observational, retrospective, cross-sectional study. Patients who underwent both optical coherence tomography (OCT) and FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…We first used novel OFR software that can precisely analyse various plaque components to study the dynamic natural morphologies and component changes in nonculprit subclinical atherosclerosis in patients with ACS based on OCT images from the subgroup data of our previous randomized controlled trial [30,31,40]. In our study, nonculprit lesions had regressed at 1-year follow-up in more than 50% of patients with ACS, even with standard LLT (statin ± ezetimibe).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We first used novel OFR software that can precisely analyse various plaque components to study the dynamic natural morphologies and component changes in nonculprit subclinical atherosclerosis in patients with ACS based on OCT images from the subgroup data of our previous randomized controlled trial [30,31,40]. In our study, nonculprit lesions had regressed at 1-year follow-up in more than 50% of patients with ACS, even with standard LLT (statin ± ezetimibe).…”
Section: Discussionmentioning
confidence: 99%
“…Both ILUMIEN OPTIS and C7-XR (Lightlab Imaging Incorporated, Westford, MA) could be applied with a 2.7F (Dragonfly OPTIS or Dragonfly Duo imaging catheter, Westford, MA) catheter with automatic pullback at a speed of 36 mm/s with continuous contrast injection (3-4 ml/s) to remove blood cells. OCT images were analysed offline using a dedicated software (OctPlus, version V2, Pulse Medical, Shanghai, China) with artificial intelligence algorithms [30,31]. Quantitative planimetry measurements were obtained by automatic border detection followed by manual correction frame by frame.…”
Section: Oct Image Acquisition and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the complex interactions exist between coronary physiology and morphological plaque characteristics, which may differ in hyperemic, non-hyperemic or computational physiological indices ( 88 ). More recently, Zeng et al ( 89 ) demonstrated that high lipid burden was associated with a numerical higher FFR value compared with OCT-derived computational FFR in assessing functional severity of coronary stenosis, which might be caused by larger luminal deformation of lipid-rich plaque.…”
Section: Qfr and Intravascular Imaging-defined Plaque Vulnerabilitymentioning
confidence: 99%